A low cost capacitive sensing system for monitoring and detecting falls of senior citizens - Khan, Sheroz; Alam, A. H. M. Zahirul (2015)
Care of senior individuals requires spontaneous and precise decisions so that life protecting and lifesaving therapy can be given on time. Research reveals that assistive technology can provide systems, which aid in prevention and detection of injuries to senior patients leading to a faster response. Falls are one of the major injuries occurring among seniors and they are not able to receive proper and timely help. This paper is based on monitoring the movement of individual senior people, living independently in their homes. The paper aims to study, design and develop a low cost reliable capacitance based sensing system for capturing human position in order to identify them, and the occurrence of fall. The sensor arrangement is done using a matrix of thin planar electrodes beneath the floor. This makes the system untraceable as well as discreet. Shading or darkness do not affect the system and also this system does not need much computing power. Computer vision does not have these advantages. Moreover, there is no need of wearing these devices and also no batteries should be charged. Here, the proposed system measures the variable voltage output in response to a change in capacitance values. Preliminary results have been obtained based on simulation and experimental setup.